CAKRAM GIZI SEBAGAI MEDIA PENYULUHAN UNTUK MENINGKATKAN PENGETAHUAN DAN POLA KONSUMSI BUAH DAN SAYUR PADA ANAK - Hafizah Hafizah; Zulfiana Dewi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2022)
Abstract One of the problems related to eating behavior is the lack of consumption of fruits and vegetables. Consumption of fruits and vegetables with a proportion of 1-2 servings/day was 67.16%, while fruit and vegetable consumption was 3-4 servings/day a week for the age group ≥5 years of 5.00%. The purpose of this study was to determine the effect of using nutritional discs in the nutrition education process on maternal knowledge and consumption patterns of fruits and vegetables for children. This type of research is an experiment with a pretest-posttest control group design. Sampling using simple random sampling technique as many as 32 people. The grouping of sample members into two different treatment groups, namely the first treatment group using nutritional disc media and the second the control group using leaflet media. Based on the results of the study, it shows that there is an increase in the average knowledge of mothers and children's consumption patterns through nutrition discs media before and after nutrition education. There was an effect of nutrition education in the intervention group on maternal knowledge, and there was an effect of nutrition education in the intervention group on children's fruit and vegetable consumption patterns. It is hoped that respondents can apply the knowledge that has been obtained after giving nutrition education using nutrition disc media.Keywords: Nutritional Discs Media, Fruit and Vegetable Consumption Patterns